A study of constructivist approach on learning outcomes among IXth standard students - Singh, K. P.; Viswanathappa, G. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
The present investigation has carried out to study the effectiveness of constructivist approach on the learning outcome in science. The design used for the study is preexperimental design i.e. one-group pretest-posttest design. The purposive sampling technique was used to select the school for the study. The Swami Vivekananda Government Model School Block- Srinagar, Makarwali situated in Ajmer of Rajasthan state was selected for the study. A group of 33, ninth standard students were chosen as the sample for the study from class IX-B. The sample included 15 boys and 18 girls in total. The achievement test (knowledge, understanding, application and skill) in science was developed by the investigator and was administered before and after the treatment. The SPSS has used to analysis the data. The statistical techniques t test, mean score and mean gain score has used to see the significance of constructive approach and gender difference from the data. The finding of the study shows constructivist approach is found to be effective in improving the learning outcomes of student in science. And also, Constructivist approach found significantly effective for both male and female group in improving their learning outcomes in science.